![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
6个回答
展开全部
(2)
y=e^x.(sinx-cosx)
y'
=[ (sinx-cosx) + (sinx-cosx)'] .e^x
=[ (sinx-cosx) + (cosx+sinx)] .e^x
=2sinx.e^x
(3)
y=tanx/x
y'
=[x(tanx)' - tanx.(x)' ]/x^2
=[x(secx)^2 - tanx ]/x^2
(4)
y=5^x +2√x +arctanx +ln3
y'
=(ln5).5^x +(1/√x) +1/(1+x^2)
(5)
y
= (x^5+√x+1)/x^3
=x^2 + x^(-5/2) + x^(-3)
y'=2x -(5/2)x^(-7/2) -3x^(-4)
y=e^x.(sinx-cosx)
y'
=[ (sinx-cosx) + (sinx-cosx)'] .e^x
=[ (sinx-cosx) + (cosx+sinx)] .e^x
=2sinx.e^x
(3)
y=tanx/x
y'
=[x(tanx)' - tanx.(x)' ]/x^2
=[x(secx)^2 - tanx ]/x^2
(4)
y=5^x +2√x +arctanx +ln3
y'
=(ln5).5^x +(1/√x) +1/(1+x^2)
(5)
y
= (x^5+√x+1)/x^3
=x^2 + x^(-5/2) + x^(-3)
y'=2x -(5/2)x^(-7/2) -3x^(-4)
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询